Peran Good Corporate Governance (GCG) Dalam Meningkatkan Nilai Perusahaan Sektor Pertambangan - Dwi Astutik; Deny Nitalia Mindrawati; Zahra Dinul K; Daniel Adi Setya Rahardjo; Pindo Asti (Universitas Boyolali, 2025)
This paper aims to examine the direct effect of Good Corporate Governance practices on firm value. Specifically, this study examines the direct effect of the role of an independent board of commissioners and an audit committee on firm value using agency theory and signaling theory. These two theories were chosen because they are able to explain managerial mechanisms such as oversight and information transparency, which can help companies reduce agency conflicts while providing positive signals to investors. The analytical method used in this study is ordinary least squares (OLS) using a quantitative approach. The sample in this study were mining companies listed on the Indonesia Stock Exchange between 2021 and 2024. The analysis results show that the presence of an independent board of commissioners and the size of the audit committee are positively and significantly correlated with firm value, thus, a strong governance structure is in line with increasing firm value. This study provides empirical contributions and public policy implications that strongly support the relevance of GCG as an important instrument in creating long-term value in companies and represents a limited literature on the influence of CG and firm value in the mining sector.